Two-year outcomes after percutaneous mitral valve repair with the MitraClip system: durability of the procedure and predictors of outcome. Issue 1 (8th April 2014) - Toggweiler, Stefan; Zuber, Michel; Sürder, Daniel; Biaggi, Patric; Gstrein, Christine; Moccetti, Tiziano; Pasotti, Elena; Gaemperli, Oliver; Faletra, Francesco; Petrova-Slater, Iveta; Grünenfelder, Jürg; Jamshidi, Peiman; et al.
Abstract : Objective: Analyse 2-year outcomes after MitraClip therapy and identify predictors of outcome. Methods: Consecutive patients (n=74) undergoing MitraClip therapy were included in the MitraSWISS registry and followed prospectively. Results: A reduction of mitral regurgitation (MR) to ≤ mild was achieved in 32 (43%) patients and to moderate in 31 (42%) patients; 16/63 (25%) patients with initially successful treatment developed recurrent moderate to severe or severe MR during the first year and only 1 patient did so during the second year. At 2 years, moderate or less MR was more frequently present in patients with a transmitral mean gradient <3 mm Hg at baseline (73% vs 23%, p < 0.01) and in patients with a left atrial volume index (LAVI) <50 mL/m 2 at baseline (86% vs 52%, p=0.03). More than mild MR post MitraClip, N-terminal probrain natriuretic peptide ≥5000 ng/L at baseline, chronic obstructive pulmonary disease (COPD) and chronic kidney disease (CKD) were associated with reduced survival. Conclusions: A mean transmitral gradient <3 mm Hg at baseline, an LAVI <50 mL/m 2, the absence of COPD and CKD, and reduction of MR to less than moderate were associated with favourable outcome. Given a suitable anatomy, such patients may be excellent candidates for MitraClip therapy. Between 1 and 2 years follow-up, clinical and echocardiographic outcomes were stable, suggesting favourable, long-term durability of the device.